Quartz accelerator of charged particles - Ivashchuk, O.O.; Shchagin, A.V.; Kubankin, A.S.; Nikulin, I.S.; Miroshnik, V.S.; Volkov, V.I.; Ionidi, V.Y.; Chepurnov, A.S.; Oleinik, A.N.; Lepeshko, D.A.; Zhukova, M.A. (Вопросы атомной науки и техники, 2020)
Results of first experiments with piezoelectric accelerator built on quartz crystals as piezoelectric elements are presented. Accelerating voltage in such quartz accelerator is produced at compression in vacuum of quartz crystals along polar axis. The construction of the quartz accelerator and results of measurements the spectra of X-ray radiation which is produced by electrons accelerated in such accelerator are described. Accelerating voltage in quartz accelerator observed in the experiment is discussed.